The choice of the medium sanation in the treatment of acute widespread purulent peritonitis by the method of laparostomy in combination with programmed of the abdominal cavity sanitation - V. V. Grubnik; O. I. Tkachenko; Y. M. Koshel; V. M. Kosovan; E. A. Koychev (Kazimierz Wielki University, 2016)
The accumulated clinical experience and analysis of our own results of treatment of patients with severe forms of acute widespread purulent peritonitis, speaks about the growing urgency of this problem. The aim of this study was determination of the most optimal medium sanation during execution programs of the abdominal cavity sanitation in acute diffuse purulent peritonitis. Was studied the treatment results of 79 patients with severe forms of acute widespread purulent peritonitis. After laparotomy and performing a biopsy was conducted qualitative and quantitative morphological study of the inflammatory process in the peritoneum on the background of the landmark of the abdominal cavity sanitation of  two groups of patients with acute widespread purulent peritonitis before and after carrying out the programmatic sanitation of the abdominal cavity, using a solution of octenidine dihydrochloride and saline solution. In the result of study, authors came to the conclusion, that the application, as it seemed different sanation mediums do not affect on the basic morphometric parameters of the studied biopsies of the peritoneum after sanitation of abdominal cavity. This confirms the theory of "mechanical purification" of the abdominal cavity, and sanitation of the abdominal cavity does not depend on the qualitative composition of the sanation medium.